2018
DOI: 10.1016/j.appet.2018.05.144
|View full text |Cite
|
Sign up to set email alerts
|

Infant hunger and satiety cues during the first two years of life: Developmental changes of within meal signalling

Abstract: Overfeeding in infancy may lead to overweight and obesity in later childhood. Mothers are advised to "tune in" to their infant's hunger, appetite and satiation cues to prevent overfeeding. The present study aimed to 1) assess stability and change in infant hunger and satiety cues (first two years of life) taken at six monthly intervals; 2) track the expression of appetite cues during the course of a meal (beginning, middle and end). Thirty-eight women (mean age 35.3 + 3.7 years) participated in the study. Moth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 26 publications
2
11
0
2
Order By: Relevance
“…Consistent with our results, previous studies observed the relationships between social skills and infant's physical development [32]. According to the Infant Research framework [33], infant social communication abilities develop in dynamic functional interactions between mothers and infants.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with our results, previous studies observed the relationships between social skills and infant's physical development [32]. According to the Infant Research framework [33], infant social communication abilities develop in dynamic functional interactions between mothers and infants.…”
Section: Discussionsupporting
confidence: 92%
“…In that case, it may preclude their potential development of caregivers' feeding responsiveness [35]. Scholars propose that maternal responsiveness to their children's expressions, such as appetite, hunger, and satiety is essential developing a healthy diet and could play an essential role in offspring weight status [32]. Besides, it is generally known that language and social competence can be simultaneously discussed as previous studies have demonstrated that children's social and language development are synchronized mainly[36];…”
Section: Discussionmentioning
confidence: 99%
“…In that case, it may preclude their potential development of caregivers' feeding responsiveness [35]. Scholars propose that maternal responsiveness to their children's expressions, such as appetite, hunger, and satiety is essential developing a healthy diet and could play an essential role in offspring weight status [32]. Besides, it is generally known that language and social competence can be simultaneously discussed as previous studies have demonstrated that children's social and language development are synchronized mainly [36]; However, no relationship between language ability and body weight was found in our study.…”
Section: Discussionmentioning
confidence: 99%
“…One interpretation of this observation is that mothers with obesity are more alert and responsive to cues for hunger and less sensitive to signs of fullness, which may result in T infant hunger than those who formula fed. The observation that breastfeeding promotes more responsive feeding has been supported by a number of studies by Shloim et al [8][9][10] and could relate to a greater level of closeness, contact and trust that their baby is capable of communicating satiety. It has also been shown that infants born to mothers at high risk of obesity were less likely to breastfeed exclusively, and less likely to believe that infants know their own hunger and satiety than mothers at low risk [11].…”
Section: Takedownmentioning
confidence: 99%